2018
DOI: 10.1021/jacs.8b10888
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of a Neutral U(II) Arene Sandwich Complex

Abstract: Reduction of IU­(NHAriPr6)2 (AriPr6 = 2,6-(2,4,6-iPr3C6H2)2C6H3) results in a rare example of a U­(II) complex, U­(NHAriPr6)2, and the first example that is a neutral species. Here, we show spectroscopic and magnetic studies that suggest a 5f46d0 valence electronic configuration for uranium, along with characterization of related U­(III) complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
109
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(129 citation statements)
references
References 22 publications
(39 reference statements)
14
109
0
1
Order By: Relevance
“…13 When only considering the E 0 value, [U II L 2 ] would be synthetically accessible using similar approach in previous studies, as well as other actinide(II) complexes. [6][7][8][9][10][11][12][13][14][15][16][17][18][19] As seen in Fig. 2a, the trend obtained in the work is approximately the same as those of previous studies of Bratsch 27 and Nugent.…”
Section: Reduction Reactionssupporting
confidence: 87%
See 1 more Smart Citation
“…13 When only considering the E 0 value, [U II L 2 ] would be synthetically accessible using similar approach in previous studies, as well as other actinide(II) complexes. [6][7][8][9][10][11][12][13][14][15][16][17][18][19] As seen in Fig. 2a, the trend obtained in the work is approximately the same as those of previous studies of Bratsch 27 and Nugent.…”
Section: Reduction Reactionssupporting
confidence: 87%
“…[14][15][16][17]19 It is worth noting that aforementioned U(II) complexes have some similarity and difference. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Firstly, a lowtemperature synthetic route was developed by applying potassium graphite (KC 8 ) to reduce respective U(III) parent. Secondly, it is found that the stability of complex was partially contributed by d back-bonds between U and Ar/Cp.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19] When an ew oxidation state is identified, one of the characteristics to be defined is the redox potential by which it is formed. [11][12][13][14][15][16][17][18][19] When an ew oxidation state is identified, one of the characteristics to be defined is the redox potential by which it is formed.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Additionally,e xamples of these new ions in other ligand environments have also been reported. [11][12][13][14][15][16][17][18][19] When an ew oxidation state is identified, one of the characteristics to be defined is the redox potential by which it is formed. Electrochemical analysiso ft he oxidation states of the rare-earth metalsa nd the actinides has historically been challenging due to the high reactivity and oxophilicity of these species.…”
mentioning
confidence: 99%
“…近年 [7] . 随后, 多个课题组先后合成几个二价铀配合物, 包括 Y•[UL E ] (L E = [( Ad,Me ArOH) 3 mesitylene] 3-, Ad = adamantyl) [8] 、 [U(NHAr iPr6 ) 2 ] (Ar iPr6 = 2,6-(2,4,6-i Pr 3 C 6 H 2 ) 2 C 6 H 3 ) [9] 、 Y•[U{N(SiMe 3 ) 2 } 3 ] [10] 和[U(η 5 -C 5 i Pr 5 ) 2 ] [11] . 研究表明, 环戊二烯基(Cyclopentadienyl, Cp)配合物中铀的电子组 态为 5f 3 6d 1 , 而芳香基(Arene, Ar)的为 5f 4 [7,10,[12][13][14] .…”
Section: 引言unclassified